Legal Protection for Creditors in Unregistered Fiduciary Agreements: A Normative Review Based on the Fiduciary Guarantee Law - Ismiati; Moh. Muhibbin; Ahmad Syaifudin (Eduvest - Journal of Universal Studies, 2026)
Sustainable economic development requires significant funding, which is often obtained through borrowing between creditors and debtors. One of the guarantee instruments in the financial world is fiduciary guarantees, which are regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees. Fiduciary guarantees provide legal protection for creditors, but if they are not registered in accordance with the provisions of the law, legal protection for creditors becomes limited. This study aims to analyze the legal position of creditors in unregistered fiduciary agreements, the legal consequences that arise for creditors, and the legal protection that can be provided. This study used a normative juridical approach with analytical descriptive analysis. Based on the results of the study, it can be concluded that unregistered fiduciary guarantees do not have executory power and preferential rights for creditors, so creditors lose the legal protection provided by the Fiduciary Guarantee Act. This makes it difficult for creditors to claim their rights in the event of a default. Therefore, it is important to ensure the registration of fiduciary guarantees so that creditors' rights are protected in accordance with applicable provisions.